Correlates of Knowledge about Sexually Transmitted Diseases (STDs) among Youths in Nepal - KC, Vikash Kumar; Karki, Shiva Bahadur; Niraula, Bipin Raj (Janapriya Journal of Interdisciplinary Studies, 2017)
Cross sectional and nationally representative sample drawn from Nepal Adolescent and Youth Survey 2011, this paper attempts to examine the correlates associated with knowledge about sexually transmitted diseases (STDs) among young population in Nepal. Univariate, bivariate and multivariate analyses have been used to examine the correlates associated with the knowledge about sexually transmitted diseases among youths. Bivariate analysis reveals that education, mass media exposure, mother’s education, marital status, ecological belts and regions are significantly associated (p<0.001). However, multivariate analysis shows that education and mass media exposure are the strong factors (p<0.001) associated with knowledge of at least one STD among youths after controlling others variables in the model. A special attention should be given to girls’ education particularly for the rural, remote and interior parts of the country. In addition, IEC through mass media may be an immediate action to improve the level of knowledge and awareness about STDs among youths in Nepal. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 101-109